Imaginary scenarios: Literature and Democracy in Europe - Heynders, Odile; Bax, Sander (Pivot: A Journal of Interdisciplinary Studies and Thought, 2016)
The main focus in this paper is on the European public intellectual: literary writers presenting their critical ideas and imaginaries on society, and critiquing the (dis)function and (dis)agreement in politics. The concept ‘imaginary scenario’ will be implemented to investigate imaginative scripts and settings constructed by authors to visualize democratic structures, as such commenting on political and social events and ideas. Two European writers from different nation-states, the French M. Houellebecq (Submission) and the Portugese Gonçalo M. Tavares (Learning to pray in the age of technique) build their novels around a Vorstellung of how (future) individuals and people in power could act and speak. Similarities and differences in these author’s strategies and visionaries will be examined. The ‘imaginary scenario’ is based on Charles Taylor (2004) and Elena Esposito (2007), and as surreal-perspective evidently tells something about the experience of the present. Our claim is that these European writers have to be considered in a critical context beyond the save haven of autonomy: in their novels they address the reader as citizen and invite him to reflect on democratic practices. Thus, these European scenarists prompt us to reconsider what it means to live in the EU and to reflect on its political realities and perspectives.